2008
DOI: 10.3892/mmr_00000051
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of combination therapy with S-1 and CPT-11 for metastatic colorectal cancer

Abstract: Abstract. We conducted a Phase I/II study of combination therapy using CPT-11 and S-1 as a first-line treatment for metastatic colorectal cancer. The 28-day treatment cycle consisted of S-1 administered orally from day 1 to 21 and CPT-11 administered intravenously on days 1 and 15. In the Phase I portion, the dose of S-1 was fixed at 80 mg/m 2 /day, while CPT-11 was administered at a starting dose of 60 mg/m 2 then stepped up in 20 mg/m 2 increments. The maximumtolerated dose was achieved at 80 mg/m 2 of CPT-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The results of 10 studies on combination therapy of irinotecan and S-1 (tegafur/gimeracil/oteracil). For each dose considered in each trial, the numbers of patients experiencing DLT events and the total numbers of exposed patients are given Ogata et al (2009) 0/3 0/3 3/4 Inokuchi et al (2006) 0/3 10/42 0/3 2/3 Goya et al (2012) 0/3 0/3 3/5 Takiuchi et al (2005) 1/6 0/3 0/4 3/6 Ishimoto et al (2009) 0/3 0/3 0/3 2/4 Kusaba et al (2010) 0 / 6 2 / 3 Nakafusa et al (2008) 7/39 2/3 Shiozawa et al (2009) 1/6 2/6 2/6 2/3 Yoda et al (2011) 0 / 3 3 / 6 Komatsu et al (2010) 1/9 1/9 0/3…”
Section: Tablementioning
confidence: 99%
“…The results of 10 studies on combination therapy of irinotecan and S-1 (tegafur/gimeracil/oteracil). For each dose considered in each trial, the numbers of patients experiencing DLT events and the total numbers of exposed patients are given Ogata et al (2009) 0/3 0/3 3/4 Inokuchi et al (2006) 0/3 10/42 0/3 2/3 Goya et al (2012) 0/3 0/3 3/5 Takiuchi et al (2005) 1/6 0/3 0/4 3/6 Ishimoto et al (2009) 0/3 0/3 0/3 2/4 Kusaba et al (2010) 0 / 6 2 / 3 Nakafusa et al (2008) 7/39 2/3 Shiozawa et al (2009) 1/6 2/6 2/6 2/3 Yoda et al (2011) 0 / 3 3 / 6 Komatsu et al (2010) 1/9 1/9 0/3…”
Section: Tablementioning
confidence: 99%
“…Nine of the cancer related genes, CHFR, p16, RUNX3, E-cadherin, MGMT, hMLH1, ABCG2, UGT1A1 and BNIP3, were chosen for methylation analysis, because frequent gene methylation has been reported in solid cancers, including CRC (5)(6)(7)(8)(10)(11)(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24). A significant correlation between gene methylation or expression and chemosensitivity to 5-FU, S-1 and CPT-11 has been reported for p16 (11), MGMT (29), hMLH1 (12), ABCG2 (16,30), UGT1A1 (14) and BNIP3 (31).…”
Section: Discussionmentioning
confidence: 99%
“…A phase I/II study assessed the toxicity and efficacy of S-1/CPT-11 combined therapy for metastatic CRC (13,25). The result showed that a response to the S-1/CPT-11 combined therapy was obtained in 19 of 33 (58%) patients without any significant toxicity, suggesting the efficacy of S-1/CPT-11 against metastatic CRC (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations